GAMBARAN DARAH Rana erythraea (Schlegel 1837) DI WILAYAH KAMPUS UNIVERSITAS RIAU PEKANBARU - Syilfia Sulastri; Titrawani '; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Rana erythraea (Schlegel 1837) is a semi-aquatic amphibian that can be used as enviromental indicator. The environmental change will result in the occurrence of changes in the health condition of frog. This research on blood profile of frog was conducted to find out about the health condition of the frog living in the area campus of Riau University. The study was conducted from August to October 2013. Twenty frogs were captured (8 males and 12 females) and frog blood was sampled from the heart using a syringe that has been moistened with EDTA. Hematological parameters calculated were the level of haematocryte, leucocryte, the number of erythrocyte and leucocyte were 10-27%, 1.00-4.16%, 170.000-670.000 cells/ml3 and 1.875-3.666 cells/ml3 respectively.